FISSIPAROUS SEA CUCUMBER (Holothuria atra) POPULATION IN NORTH LOMBOK, INDONESIA - Indriana, Lisa Fajar; Firdaus, Muhammad; Supono, -; Soffa, Fawzan Bhakti (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
Sea cucumbers belonged to the species of Holothuria atra are one of the holothurians that could reproduce asexually through fission particularly when their ambient environments are not optimum to reproduce sexually. The reproductive pattern of H. atra has been shown to correlate with to the condition of H. atra population as well as their habitats and environments. This study aims to investigate the asexual reproduction and fission rate of H. atra in Tanjung, North Lombok, Indonesia. We conducted surveys in February, May, July, August, September and December 2016 by applying the free collection method. A total of 1,383 individual H. atra were collected consisting of 931 intact or normal individuals, 174 anterior individuals, 261 posterior individuals and 17 uncategorized individuals. Fissioned H. atra were found in every sampling conducted in the six different months with fission rates range from 5.53 to 30.40%. This research shows that the population of H. atra in Tanjung, North Lombok, are susceptible to asexual reproduction (fission). Fission rate value of > 5% is associated with an adaptation mechanism of H. atra to maintain their population in the wild. Further investigation on the environmental conditions stimulating H. atra fission is needed to understand the reproduction and population dynamic of this species in Tanjung waters.